Examining gender based violence and abuse among Liberian school students in four counties: An exploratory study. (June 2015) - Postmus, Judy L.; Hoge, Gretchen L.; Davis, Rebecca; Johnson, Laura; Koechlein, Elizabeth; Winter, Samantha
Abstract: The purpose of this article is to uncover the extent of sexual gender based violence (GBV) experienced by a convenience sample of students from select counties in Liberia and to understand the disclosure experiences of those victims willing to come forward. Girls ( n  = 758) and boys ( n  = 1, 100) were asked about their sexual GBV experiences including their disclosure experiences, if applicable. Results indicated that sexual violation (i.e., peeping or inappropriate touching) was found among both girls and boys. Sexual coercion (i.e., forced sex) was more prevalent than transactional sex (i.e., trading sex for grades or money). Both sexual coercion and transactional sex were reported by more girls than boys, yet the rates for the most severe form of sexual violence (i.e., sexual coercion) were high for both girls (30%) and boys (22%). When students were asked if they told anyone, 38% reported that they did disclose their experiences. This study contributes to a small but growing body of research to document the prevalence and types of sexual violence against children in Liberia. Consistent with other studies, the evidence shows that sexual violence against boys and girls is occurring at alarming rates.